Enhanced thermal conductivity of polyimide composite film filled with hybrid fillers. (October 2021) - Li, Ruiyi; Ding, Chengcheng; Yu, Juan; Wang, Xiaodong; Huang, Pei
In this article, the polyimide (PI) composite films with synergistically improving thermal conductivity were prepared by adding a few graphene nanoplatelets (GNP) and various hexagonal boron nitride (h-BN) contents into the PI matrix. The thermal conductivity of PI composite film with 1 wt% GNP and 30 wt% h-BN content was 1.21 W(m·k) − 1, which was higher than that of the PI composite film with 30 wt% h-BN content (0.45 W(m·k) − 1 ), the synergistic efficiency of GNP under various h-BN content (10 wt%, 20 wt%, and 30 wt%) were 1.70, 2.71, and 3.09, respectively. And it was found that the increased h-BN content can suppress the dielectric properties caused by GNP in the matrix. The dielectric permittivity and dielectric loss tangent of 1 wt% GNP/PI composite film were 10.69, 0.661 at 10 3 Hz, respectively, and that of the 30 wt% h-BN + GNP/PI composite film were 4.29 and 0.1367, respectively. Moreover, the mechanical properties of the PI composite film were suitable for practical applications. And the heat resistance index and the residual rate at 700°C of PI composite film increased to 326.8°C, 74.43%, respectively, and these of PI film were 292.6°C and 59.26%. Thus, it may provide a reference value for applying the filler hybridization/PI film in the electronic packaging materials.